Rapid Drying of Northeast India in the Last Three Decades: Climate Change or Natural Variability?. Issue 1 (15th January 2019) - Choudhury, B. Abida; Saha, Subodh Kumar; Konwar, Mahen; Sujith, K.; Deshamukhya, Atri
Abstract: Northeast India (NEI), the wettest place on the Earth, has experienced a rapid decrease in summer monsoon rainfall (about 355 mm) in the last 36 years (1979–2014), which has serious implications on the ecosystem and the livelihood of the people of this region. However, it is not clear whether the observed drying is due to anthropogenic activities or it is linked with the global natural variability. A diagnostic model is employed to estimate the amount of recycled rainfall, which suggests that about 7% of the total rainfall is contributed by the local moisture recycling and decrease in recycled rainfall is about 30–50 mm. Using gridded observed rainfall and sea surface temperature data of the last 114 years (1901–2014), here we show that the recent decreasing trend of NEI summer monsoon rainfall is rather associated with the strong interdecadal variability of the subtropical Pacific Ocean. The strong interdecadal variability over NEI suggests a possibility of skillful decadal prediction of the monsoon rainfall, which may have important implications in terms of long‐term planning and mitigation. Key Points: Rapid drying of Northeast India in the last three decades is found The estimated recycled rainfall is rather small, which suggests a minimum contribution of local feedback on the observed drying trend This drying is found to be a part of interdecadal natural variability associated with the Pacific decadal oscillation